Social networks and popular understanding of science and health : sharing disparities - Southwell, Brian G. [ (Brian Glen)] , 1974- (RTI, 2013)
Utilization of social media for teaching people about science and health in the 21st century may seem like an obvious strategy. However, systematic reliance on social networks to spread information may be a recipe for inequity. An increasing body of research suggests that some people are much less likely than others to share information in a peer-to-peer environment. This book explores why these information-sharing patterns persist, why they matter to society, and what, if anything, can be done to address these tendencies